The Benefits and Challenges of Preconsent in a Multisite, Pediatric Sickle Cell Intervention Trial. Issue 9 (15th April 2016) - Nimmer, Mark; Czachor, Jason; Turner, Laura; Thomas, Bobbe; Woodford, Ashley L.; Carpenter, Karli; Gonzalez, Victor; Liem, Robert I.; Ellison, Angela; Casper, T. Charles; Brousseau, David C.; ,
Abstract : Enrollment of patients in sickle cell intervention trials has been challenging due to difficulty in obtaining consent from a legal guardian and lack of collaboration between emergency medicine and hematology. We utilized education and preconsent in a pediatric multisite sickle cell intervention trial to overcome these challenges. Overall, 48 patients were enrolled after being preconsented. Variable Institutional Review Board policies related to preconsent validity and its allowable duration decreased the advantages of preconsent at some sites. The utility of preconsent for future intervention trials largely depends on local Institutional Review Board policies. Preeducation may also benefit the consent process, regardless of site differences.